Spatial targeting of land rehabilitation: a relational analysis of cropland productivity decline in arid Uzbekistan - Dubovyk, Olena; Menz, Gunter; Conrad, Christopher; Lamers, John P. A.; Lee, Alexander; Khamzina, Asia (ERDKUNDE, 2013)
Irrigated croplands in Central Asia are highly prone to land degradation due to their environmentally fragile physical settings and intensive agricultural practices. This study: (i) assesses the state of croplands in irrigated areas in northern Uzbekistan, based on the time series of MODIS-NDVI imagery; (ii) analyzes relationships between the identified trend of cropland degradation and soil quality, terrain characteristics, population density, and land use; and (iii) synthesizes the results which form the basis for recommendations on spatial targeting of land rehabilitation measures. The NDVI-based cropland degradation assessment revealed a significant decline of cropland productivity across 23% (94,835 ha) of the arable area in the study region between 2000 and 2010. We conclude that the degraded cropland identified within areas of high population density and with better quality soils, can be prioritized for rehabilitation measures. For degraded croplands located in sparsely populated areas with poorer quality soils, other alternatives (such as leaving cropland fallow) may be more effective depending on the severity of degradation and economic viability of rehabilitation options.